ANALISIS KEBUTUHAN E-BOOKLET BERNUANSA EMOTIONAL SPIRITUAL QUOTIENT PADA MATERI SISTEM REPRODUKSI MANUSIA DI SMAN 1 LUBUK BASUNG - Zulyusri; Cemara (CV. Jendela Gagasan, 2025)
This research aims to analyze the need for the development of an Emotional Spiritual Quotient (ESQ) themed e-booklet on human reproductive system material at SMAN 1 Lubuk Basung using a qualitative descriptive method involving 32 Phase F students and one biology teacher through observation, interviews, and documentation. The results show that 46% of the students considered the human reproductive system to be the most difficult material, the booklet was the most favored learning media (46%), and all students (100%) supported the development of the ESQ-themed e-booklet with a preference for a light green design (46%). The teacher also emphasized the need for media that is concise, engaging, and equipped with illustrations to facilitate student understanding. Thus, the development of the ESQ-themed e-booklet is considered relevant to assist in understanding complex concepts while instilling emotional and spiritual values in biology learning.